Income diversification and the rural non-farm economy - Paudel, Susan; Filipski, Mateusz J.; Minten, Bart (International Food Policy Research Institute, 2022)
This paper empirically investigates the role of off-farm and non-agricultural activities in Myanmar’s rural sector, based primarily on the nationally representative MLCS 2016/17. We find evidence of extensive diversification: rural households are generating about 25 percent of their income on the farm; the remaining income comes from wage labor (34 percent), non-agricultural businesses (27 percent), and about 15 percent from passive sources (remittances and others). More than half of rural households engage in non-farm activities. Despite this large participation, the non-farm sector is informal and has yet to reach its full job-creating potential. Diversification is broad-reaching, and prevalent at all levels of income; however, wealthier households participate more heavily in the non-farm sector. Land constraints, household size, education levels, and gender all appear correlated with households’ propensity to diversify. Since the start of the twin crises, we continue to see significant diversification in rural incomes and all sectors – farm and non-farm – suffering very similar income shocks.